(untitled) (Revista de Artes Marciales Asiáticas, 2018)
Taekwondo has been popular for decades and its practice has become part of Western countries. One of its lines of expansion and introduction in the West, like other martial arts, was the philosophical-religious sphere, which has been promoted by the sports federations, and has emphasized aspects related to Taoism, Buddhism, Confucianism and Korean national religions. I rely on a study of documentary sources, contextualized within an ethnographic investigation, to analyze the religious elements that appear in the material culture, values, techniques and practices that have been developed in the gymnasiums, as well as the symbolic exegeses that are made from official institutions.